Blood simple - Barenholtz, Ben, 1935-; Coen, Joel.; Coen, Ethan; Getz, John, 1946-; McDormand, Frances; Hedaya, Dan.; Williams, Samm-Art.; Walsh, M. Emmet, 1935-; River Road Productions; MGM DVD (Firm); Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, CA : MGM DVD : Distributed by Twentieth Century Fox Home Entertainment, 2008)
When Marty, the owner of a Texas backwoods bar, hires a man to kill his cheating wife and her boyfriend, he opens a door into the criminal world that he'll never be able to shut. The sleazy hit man decides instead to shoot Marty, thereby collecting his unearned fee and eliminating the only person who could implicate him-- or so he thinks.
Title from container.
Originally released as a motion picture in 1985.
Director of photography, Barry Sonnenfeld ; music, Carter Burwell.
John Getz, Frances McDormand, Dan Hedaya, Samm-Art Williams, M. Emmet Walsh.
MPAA rating: R.
DVD, region 1, widescreen (1.85:1) presentation; Dolby Digital mono., single layer, NTSC.
Keywords: Murder for hire -- Texas -- Drama; Adultery -- Texas -- Drama; Private investigators -- Texas -- Drama; Deception -- Texas -- Drama; Murderers -- Texas -- Drama; Films for the hearing impaired; Thrillers (Television programs); Thrillers (Motion pictures); Feature films